The Effectiveness of Using YouTube Videos to Enhance Vocabulary Memorization Skills among Students at MA Manba’ul Ulum - Sri Nurhikmah; Karyawan Putraidi; Hamjah Hamjah (Universitas Qamarul Huda Badaruddin, 2025)
This study investigates the effectiveness of YouTube videos in improving students’ vocabulary memorization skills. Conducted at MA Manba’ul Ulum, the research employed a quasi-experimental design involving two groups: an experimental group taught using an animated YouTube listening video and a control group taught using traditional methods. The sample consisted of 30 tenth-grade students divided equally into two groups. Data were collected through pre-tests, treatments, post-tests, and student perception questionnaires. Results revealed significant improvement in the experimental group, with mean scores rising from 49.67 in the pre-test to 86.67 in the post-test, compared to the control group’s increase from 49.33 to 60.53. Gain score analysis showed a normalized gain of 0.74 (high) for the experimental group and 0.22 (low) for the control group. Independent samples t-test confirmed a significant difference (p < 0.05). These findings support multimedia learning theory, demonstrating that YouTube’s visual-auditory content effectively enhances vocabulary retention and student engagement.